A novel treatment for management of a trapped placenta using intracervical nitroglycerin tablets. (6th September 2013) - Rodgers, Blake Conley; Pasternak, Adam; Gray, Richard
Abstract : A 34-year-old gravida 2, para 1 woman delivered a viable male infant and developed retained placenta due to entrapment. A nitroglycerin tablet was used to relax the lower uterine segment and cervix, which allowed the placenta to pass through the cervix for delivery. The nitroglycerin tablet was placed in the cervix and held in place by the delivering physician as it dissolved. Soon after administration, the intact placenta delivered. The patient did not experience the typical side effects of headache, asymptomatic decrease in blood pressure, hypotension, palpitations or dizziness that can be associated with administration of nitroglycerin. We suspect that this novel localised route of nitroglycerin administration may be an effective management strategy to treat trapped placenta while minimising side effects. However, the outcomes of this treatment would require further study.